Kontradiksi Mushaf Al-Quran Standar Indonesia Dari Penulisan Kaidah Imla Hamzah Al-Qath’i & Al-Washli Pada Surah Al-Kahfi - Rasikhullah, Ahmad Najid; Ahmad, Lalu Turjiman (Universitas Muhammadiyah Gorontalo, 2023)
The background of this research is the existence of contradictive from the imla rules regarding hamza qath'i and washli contained in the Indonesian standard Qur'anic manuscripts and researchers are trying to uncover these anomalies in surah al-Kahf. It is very unfortunate that the application of the imla rules of hamzah qath'i and washli is not taken into account by the Indonesian standard Qur'anic manuscripts, even though the hamzah qath'i and washli in the imla rules have a special place in the Arabic writing system. This deviation can cause the reader to get stuck in reading the verse, because there is no clear difference in writing between hamzah qath'i and wasli. The method used is descriptive qualitative approach method. Furthermore, the analytical method used is content analysis rules. From the results of the study it shows that in Surah al-Kahf in the Indonesian standard Mushaf there are 116 words that have deviations from the imla rules which are dominated by 52 isim, 44 fi'il and 20 letters. This is due to the preference of the state, printing and school of thought in writing of the Koran.